9C.06: COMPARISON BETWEEN CARDIOLOGY AND ENDOCRINOLOGY PHYSICIANS IN THEIR MANAGEMENT OF HYPERTENSION AND DIABETES MELLITUS. (June 2015) - Wang, J.; Song, J.; Huang, Q.F.; Li, L.H.; Sheng, C.S.; Li, Y.; Ji, L.N.; Kang, Y.
Abstract : Objective: To investigate the comorbidity rate of diabetes or hypertension in cardiology outpatients with hypertension or endocrinology outpatients with diabetes. Design and method: A multi-center, cross-sectional, non-interventional disease registry study has been conducted in a sample of 2, 510 outpatients enrolled from 20 cardiology and 20 endocrinology departments, respectively. The demographic data, medical history and physical examination results were recorded and questionnaire on illness perception were conducted. Diagnosis of hypertension and diabetes were determined by measured blood pressure and HbA1c (or FBG). Obesity, metabolism syndrome (MS), and consumption of tobacco and alcohol were used to estimate CVD risk. The tests of microalbuminuria and ECG were performed by central lab, and the treatment pattern was evaluated by patient's chart or self-reporting. Results: The proportion of hypertension in 1180 diabetic patients was 59.0% (95% CI, 56.1%-61.8%); meanwhile the proportion of diabetes in 1330 hypertensive patients was 32.6% (95% CI, 30.1%–35.2%). The proportions of patients with MS, tobacco and alcohol consumption were higher in endocrinology than cardiology group (61.7%, 17.8% and 16.9% vs. 55.6%, 17.0% and 16.8% respectively), while for patients with obesity was opposite (48.6% vs. 52.0%). The prevalence of albuminuria (15.4% vs. 21.3%; P = 0.39) and ECG-left ventricular hypertrophy (8.0% vs. 7.9%; P = 0.99) between the two groups was similar. In previously diagnosed hypertensive patients in cardiology (n = 1330) and endocrinology department (n = 607), in spite of similar antihypertensive treatment rate (87.7% vs. 88.1%; P = 0.82), the proportion of antihypertensive monotherapy was lower (37.1% vs. 56.7%; P < 0.0001) and combination therapy was higher (50.6% vs. 31.5%; P < 0.0001) in cardiology department than endocrinology department. Conclusions: In spite of similar treatment pattern, the intensity of treatment differed substantially between cardiologists and endocrinologists. In addition, the real-life medications may be different from guideline recommendations, which indicate an important need to further bridge the gap.